KEPUASAN KERJA MEMEDIASI FAKTOR-FAKTOR YANG MEMENGARUHI KOMITMEN AFEKTIF PADA PT XYZ - THIARA CHAHYA NABILLA; WASISTO RUSWIDIONO (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2026)
This study aims to analyze the effects of recruitment and selection, training and socialization, and employee security on employees’ affective commitment, with job satisfaction as a mediating variable, among employees of PT XYZ. Headquarters. The population of this study consisted of 264 PT XYZ employees, with a sample of 116 respondents selected using purposive sampling technique. Data were collected through the distribution of questionnaires using a Likert scale to measure each research variable. Data analysis was conducted using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) approach. The results of the study indicate that recruitment and selection, training and socialization, as well as employee security have a effect on job satisfaction. Recruitment and selection and employee security also have a effect on affective commitment, while training and socialization do not have a direct effect on affective commitment. Job satisfaction has a effect on affective commitment. Furthermore, job satisfaction does not mediate the relationship between recruitment and selection and affective commitment, but it mediates the effects of training and socialization and employee security on affective commitment.